Central Vigilance Committee Propaganda Week: 2022 Overview - Rubaye, Joudah; Araj , Ahmed (Journal of Social Science and Humanities, 2024)
There are very few countries which are free from corruption but there is hardly any developing country which is free from corruption. India is also amongst those countries which is a developing country and not fully free from corruption. In order to control the corruption, the government of India took several steps and set up an independent commission named as Central Vigilance Commission. The Commission organised an awareness week in the year 2022 which was held during October 31, 2022 to November 6, 2022. The theme for the week was “Corruption free India for a developed nation”. In the present paper, we have tried to explain certain aspects of Central Vigilance Commission Awareness Week 2022.